2018
DOI: 10.1097/j.pain.0000000000001326
|View full text |Cite
|
Sign up to set email alerts
|

Lionfish venom elicits pain predominantly through the activation of nonpeptidergic nociceptors

Abstract: The lionfish (Pterois volitans) is a venomous invasive species found in the Caribbean and Northwestern Atlantic. It poses a growing health problem because of the increase in frequency of painful stings, for which no treatment or antidote exists, and the long-term disability caused by the pain. Understanding the venom's algogenic properties can help identify better treatment for these envenomations. In this study, we provide the first characterization of the pain and inflammation caused by lionfish venom and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…The culture of dorsal root ganglion (DRG) neurons was performed as previously described. 22 Briefly, DRG were dissected from 3-month-old male mice, and placed in sterile HBSS at 4°C. Enzymatic dissociation was performed with 0.2% type IV collagenase and 0.2% dispase for 105 minutes, followed by a 5-minute treatment with 0.25 mg/mL trypsin.…”
Section: Methodsmentioning
confidence: 99%
“…The culture of dorsal root ganglion (DRG) neurons was performed as previously described. 22 Briefly, DRG were dissected from 3-month-old male mice, and placed in sterile HBSS at 4°C. Enzymatic dissociation was performed with 0.2% type IV collagenase and 0.2% dispase for 105 minutes, followed by a 5-minute treatment with 0.25 mg/mL trypsin.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that pore formation might be the underlying cause [43,55], but there is also evidence against this hypothesis. For instance, while investigating the pain caused by the lionfish P. volitans venom, [74] found that the heat-labile, protein components responsible for this activity appear to act specifically on neuropeptidergic nociceptors, although the identity of these components has yet to be determined.…”
Section: Pain-inducing and Inflammatory Activitiesmentioning
confidence: 99%
“…Stingrays, spine fish such as the stonefish and lionfish, sea urchins, sponges, and octopuses are common culprits for envenomation injuries. 4 The stonefish, Synanceia verrucosa , is one of the more venomous fish to be found in the Pacific basin (Figure 1). The fish's vernacular name derives from its mottled brown-green pattern, giving it the ability to camouflage itself among stones and corals.…”
mentioning
confidence: 99%
“…5 The dorsal spine's verrucotoxin acts on beta-adrenergic receptors and induces a cascade of histamine and catecholamines release. 4,6-8…”
mentioning
confidence: 99%
See 1 more Smart Citation